Esophageal microflora in esophageal diseases - Zou, Qian; Feng, Lijuan; Cai, Xunchao; Qian, Yun; Xu, Long (Frontiers in Cellular and Infection Microbiology, 2023)
With the development of endoscopic technology, an increasing number of patients with esophageal disease are being diagnosed, although the underlying pathogenesis of many esophageal diseases remains unclear. In recent years, a large number of studies have demonstrated that the occurrence and development of various intestinal diseases were related to intestinal flora. As a result, researchers have shifted their focus towards investigating esophageal flora to better understand the pathogenesis, early diagnosis, and treatment of esophageal diseases. This paper reviewed the normal esophageal flora and the changes of esophageal flora under different esophageal disease states. It was observed that there are distinct differences in the composition of esophageal microflora among Gastroesophageal Reflux, Barrett’s esophagus, eosinophilic esophagitis and normal esophagus. The normal esophageal flora was dominated by gram-positive bacteria, particularly Streptococcus, while the esophageal flora under esophagitis was dominated by gram-negative bacteria. Furthermore, the diversity of esophageal flora is significantly decreased in patients with esophageal cancer. Several potential microbial biomarkers for esophageal cancer have been identified, among which Fusobacterium nucleatum showed a close association with esophageal squamous cell carcinoma’s pathological stage and clinical stage.